Case report: Sudden unexpected death due to tuberculous myocarditis involving sinus node at autopsy - Zhang, Le; Yan, He; Wang, Yufang; Huang, Feijun (Frontiers in Cardiovascular Medicine, 2023)
Tuberculous myocarditis (TM) is an extremely rare manifestation of Mycobacterium tuberculosis (TB) infection. Although TM is a critical cause of sudden cardiac death, only a few cases have been reported. We report the case of an older patient with pulmonary TB with a history of fever, chest tightness, paroxysmal palpitations, and electrocardiographic evidence of sinus node conduction abnormalities on admission. Although emergency physicians observed these unusual clinical manifestations, no timely differential diagnosis was made nor interventions were performed. A definitive diagnosis of TM and histopathological findings compatible with sinus node involvement were made based on autopsy outcomes. Herein, we describe the clinical presentation and pathological features of a rare form of Mycobacterium TB. In addition, we provide an overview of issues related to the diagnosis of myocardial TB.